Impact of wildfire on interdune ecology and sediments: an example from the Simpson Desert, Australia - Craig L. Strong; Joanna Bullard; Chloe Dubois; Grant H. McTainsh; Matthew Baddock (2010)
The stability of many sand dunes and their interdunes is dependent on vegetation and surface crust cover. When this cover is removed, the sand can be activated and fine sediments deflated making the dunefields into sources of dust. This paper reports the impact of devegetation by wildfire on an interdune in the Simpson Desert, Australia. The fire occurred in 2001 and six years after the event pronounced differences between a pair of burnt and unburnt sites was clearly discernible. The variables examined included vegetation assemblage, cyanobacteria abundance and sediment aggregation, particle-size distribution and colour; but whether they apply to all such situations is uncertain. Rate of recovery has been slow and the differences are likely to have been sustained by a combination of negative feedback processes and climate.